The therapeutic uses of balneotherapy (Payesh, 2003)
Balneotherapy involves immersion of the patient in mineral water baths or pools. The mechanisms by which broad spectrums of diseases are alleviated by balneotherapy have not been fully elucidated. They probably incorporate chemical, thermal, mechanical and immunomodulatory effects. In this article the dermatologic and the general uses of this mode of treatment is explained. A sketch of its resources in Iran is given and some recommendations about improvements that can be made on the use of this national wealth are also proposed.